Microbiota-derived extracellular vesicles cargo composition analysis using hTLR cell lines - Isola, Anna (My University, 2022)
Bacterial cells interact with other bacteria and their host cells via direct interaction or the secretion of soluble components, such bacterial extracellular vesicles (BEVs). BEVs distribute a portion of the parent bacterium biological content into the extracellular environment, which are detected by Toll-like-receptors (TLRs) and NOD-receptors. The aim of this study was to investigate the composition and molecule concentration of BEVs derived from intestinal microbiota of untreated lung cancer patients using hTLR cell lines. Even if BEV were examined through proteomics, many microbial components would remain undetected due to their molecular nature. First, the functionality of the Commercial HEK-Blue™ hTLR and hNOD cell lines lines was tested with their ligands. After that, the BEVs were isolated from the fecal samples of untreated lung cancer patients, and the quality was checked using transmission electron microscopy, nanoparticle tracking analysis and Nanodrop protein concentration measurement. After that, the cell lines were tested with isolated BEVs, and the activation of hTLR was determined by measuring the SEAP by spectrophotometer. The results anticipate that hTLR5 cells recognized it ligands statistically significantly in all five samples. On the other hand, hTLR4 recognized its ligands statistically significantly only in two samples from five. The experiment showed a dose dependent response - the higher the BEV concentration, the greater the response in most of the samples. The results also suggest individual variability in BEV content, as the response was different between patients. However, more research is needed to conclude the role of BEVs in cancer.
Keywords: TLR cells, bacterial extracellular vesicles, lung cancer